(untitled) (International Journal of Engineering and Computer Science, 2015)
Nowadays graphical analysis has become the centrepiece of many of the studies & common day problems. Because of the ability of the graph to adept & contain data of various forms & then interpret information it is in demand everywhere, many of the big problems are being analysed through graphical networks. Graphical data mining a branch evolved out of data mining has today become such a vast subject of study, research, analysis & case-review. This in itself shows the broad scope on which graphs, graphical analysis & graphical mining is being carried out today. The basic reason for this popularity of graphs is their ease with which they can accommodate data of various types & then can give result across various domains. So in such an environment it becomes equally important to study various metrics of graph that help in such studies. Modularity is one of those metrics, whose importance has grown manifold in studying & researching social networks, behavioural pattern networks & geographical networks. In this study a force directed approach has been used to analyse modularity in a graph since it facilitates the dynamic structure of graphs that changes with respect to force applied on it similarly like a real time graphical pattern changes. Modularity is one property which can be used in multiple networks to study & analyse various parameters on which efficiency & capacity of networks is evaluated. Also with the advent of big data, business intelligence the need for information which gives multi-dimensional & multi-value relationships has grown manifold & graphical analysis especially in terms of modularity or community detection can give us plenty of such information. In this paper a very novel & realistic approach has been taken that takes into account the ever changing & dynamic nature of real time networks, based upon that a force directed approach has been taken which involves calculating the force exerted on graph at any time then finding corresponding modularity for that force. Three case of force have been analysed all for same graph to differentiate the effect of force on same graph. Three different types of forces act in a graph – attractive forces, repulsive forces & displacement force.